Application of the Ansys Fluent program for modelling environmental phenomena in a living room - Mariusz Kosiń (Budownictwo o Zoptymalizowanym Potencjale Energetycznym, 2021)
The article presents a three-dimensional numerical analysis of heat and humidity parameters carried out for a living room in a multi-family building. The aim of the analysis was to compare alternative heating methods with the existing one. Two cases were included in the analysis: case I – the existing state, case II – the existing state with an additional panel heater. In order to verify the numerical analysis for case I, the temperature and relative humidity were measured. During the heating period, the thermal conditions in the room did not favor the comfort of users, especially in one part of the room. The study may be a tool for future research related to the implementation of the climatic conditions of rooms with similar structural and functional features.